Is it possible to keep heritage landscapes original functions? Remarks on land degradation threats and monitoring indicators - Capelo, Sofia (2012)
The most important value contained in the territory is the cultural landscape in which heritage appears as the structuring value in its invention. In fact, the authors have been studying problems concerning the valorisation and sustainable development of heritage landscapes, through cultural parks and related monitoring indicators, and often facing problems how to deal with land degrading problems. Those are clearly related not only with the future of heritage landscapes, but also concern the improvement of rural population quality of life, land’s memories preservation and sustainable development new practices. This challenge is particularly important what Mediterranean landscapes concern because they are disturbance-dependent features modified by anthropogenic factors since millennia and its ecodiversity is particularly threatened. Therefore finding out and developing new means of land management is a central issue specially in the context of the actual rural world paradigm, where farmers need to move towards multifunctional activities and society is demanding both a broad spectrum of products and a high environmental and landscape quality level. That’s why land management policies and planning have to deal with the maintenance of landscape original functions, monitoring indicator the authors are analysing knowing the numerous factors of landscape degradation.